과실 수입 파급영향 분석과 대응방안 - 김경필 (한국농촌경제연구원, 2006)
This study aims to estimate the impact of fruit imports on Korean fruit industry and to suggest the strategies to cope with the opening of the Korean fruit market. The items analyzed in this research are apple, pear, mandarine, grape, peach and sweet persimmon. The Korea Rural Economic Institute-Commodity Model 2005(KREI-COMO 2005) was utilized to estimate the effect. The analyzed period is from 2008 to 2017(For 10 years). In case of permitting fruit imports in the year of 2012, the production value of apple, pear and mandarine will respectively decrease by 57 percent, 42 percent, 32 percent in comparison with their production values of maintaining import prohibition in 2017. At the same condition, the production value of grape and peach will decrease by 11 percent, 8 percent respectively. In summary, it turns out that the amount of damage of apple, pear and mandarine is larger than that of grape and peach. Therefore, the items such as apple, pear, and mandarine must be pursued high standard restructuring. Also, In order to secure restructuring period, these items should be treated as sensitive products on the negotiation of DDA and FTA. And, if the price and the amount of income go down rapidly, Income Safety-Net Program should be introduced. Researchers: Kim Kyung-Phil, Lee Won-Jin, Park Jae-Hong, Park Mi-Sung E-mail address: kkphil@krei.re.kr